Arctic Laboratory. A History (1947-1966) of the Naval Arctic Research Laboratory at Point Barrow, Alaska. - Reed,John C.; Ronhovde,Andreas G. (1971)
The book tells the story of the people who made the laboratory one of the most successful and most respected Arctic research facilities in the world. It probes their successes, failures, frustrations, and disasters, and focuses on the problems that administrators and researchers alike had to face and solve. The research programs and their value are described and assessed in terms of individual achievement and scientific contribution. The stories and recollections of the laboratory's personnel provide a human element that is missing in most historical books. (Author)